MEASURING SUPPLY CHAIN EFFICIENCY: A DEA APPROACH - Mishra, Rohita Kumar (2012)
Supply chain performance depends on the efficiency of supply chain. The efficiency depends on the utilized inputs and the outcome. In this paper an attempt has been taken to measure the efficiency of supply chain. We have taken the case of pharmaceutical industry of India. Efficiency of supply chain has been measured by taking inputs and outputs. The average technical efficiency score obtained through CRS model is 0.868, indicating scope for lots of improvement for the Pharmaceutical companies